Fiber material for shielding terahertz waves and preparation method and application thereof
By wrapping the nanocellulose shell layer on a two-dimensional layered material, the core-shell structure fiber material is prepared, which solves the problems of low mechanical properties and poor flexibility of existing electromagnetic shielding materials, and realizes efficient terahertz wave electromagnetic shielding and excellent mechanical properties.
Patent Information
- Application Number
- CN202411615423.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing electromagnetic shielding materials have low mechanical properties and poor flexibility, making them difficult to be used in the field of wearable electromagnetic protection.
A two-dimensional layered material such as Ti3C2Tx MXene or reduced graphene oxide is used as the core layer to wrap the nanocellulose shell layer, and a core-shell structure fiber material is prepared by coaxial wet spinning technology.
It has achieved excellent electromagnetic shielding performance of fiber materials in the 0.1~1.5 THz band, with an average shielding effect of 47.61dB, and excellent mechanical properties, tensile strength can reach 161.6MPa, and elongation of break of up to 5%.
Smart Images

Figure CN119465440A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electromagnetic shielding materials, and in particular to a fiber material for shielding terahertz waves, a preparation method thereof, and an application thereof. Background Art
[0002] With the advancement of wireless communication technology from the fifth generation (5G) to the sixth generation (6G) and the development of mobile electronic devices, the communication frequency band has expanded from the gigahertz (GHz) to the terahertz (THz) band. Terahertz (THz) waves have the characteristics of high speed, low latency and high-precision transmission, which has greatly promoted the innovation of wireless communication technology. However, while improving communication efficiency, the key components in the mobile communication network (mobile stations, base stations and mobile switching centers) inevitably generate long-term and continuous electromagnetic radiation, which poses an increasingly severe challenge to human health protection, information security maintenance and stable operation of equipment components.
[0003] As a focus of frontier exploration, smart wearable shielding devices are developing rapidly towards low power consumption, high integration, strong human-computer interaction and low cost. However, traditional electromagnetic interference shielding materials have high density and poor processability, which cannot meet the requirements of smart wearable devices. Lightweight and efficient new electromagnetic shielding materials, such as two-dimensional (2D) layered materials MXene and graphene oxide (GO), have large aspect ratios (≤10 6 ), high specific surface area (more than 1000m 2 / g) and good electrical conductivity (up to 10 7 S / m). Based on their conductivity and unique layered structure, 2D layered materials MXene and reduced graphene oxide (rGO) have outstanding performance in electromagnetic interference shielding. However, MXene and reduced graphene oxide have low mechanical properties and poor flexibility due to high porosity, low orientation and weak interlayer van der Waals (vdW) interaction, which limits their flexible application in smart wearable shielding devices.
[0004] Based on this, developing a terahertz wave shielding fiber with excellent electromagnetic shielding performance, excellent flexibility and adaptability, and using it as a raw material for the preparation of smart wearable devices can maximize the comfort, functional integration and environmental adaptability of smart wearable devices. It is not only an important guarantee for the security of future communication technology, but also a key step in promoting the smart wearable industry to a new level. Summary of the invention
[0005] The present application provides a fiber material for shielding terahertz waves, a preparation method and application thereof, aiming to solve the problems of existing electromagnetic shielding materials having low mechanical properties, poor flexibility and being difficult to be used in the field of wearable electromagnetic protection.
[0006] In order to achieve the above objectives, the present application adopts the following technical solutions.
[0007] In a first aspect of the present application, a fiber material for shielding terahertz waves is provided, which is a coaxial core-shell structure, wherein the core layer is a two-dimensional layered material, and the shell layer is nanocellulose;
[0008] The two-dimensional layered material includes Ti3C2T x MXene or reduced graphene oxide.
[0009] Preferably, the radius of the core layer is 60-65 μm, and the radius of the shell layer is 65-70 μm.
[0010] The second aspect of the present application provides a method for preparing the above-mentioned fiber material for shielding terahertz waves, characterized by comprising:
[0011] The core spinning solution is prepared by using two-dimensional layered materials, and the shell spinning solution is prepared by using nanocellulose;
[0012] The core layer spinning solution and the shell layer spinning solution are coaxially wet-spinned to prepare precursor fibers, which are solidified in a coagulation bath and dried at low temperature to obtain fiber materials.
[0013] Preferably, the core layer spinning solution is Ti3C2T x MXene spinning solution, the preparation method thereof comprises:
[0014] Ti3C2T x MAX is chemically etched by an etchant, and the etchant is removed by centrifugation and water washing; anhydrous ethanol is then added for intercalation treatment, and the precipitate is collected by centrifugation to obtain a multilayer Ti3C2T x MXene;
[0015] Towards multilayer Ti3C2T x Deionized water was added to MXene, and the black upper liquid was collected after multiple centrifugation to obtain Ti3C2T x MXene spinning solution.
[0016] Preferably, the core layer spinning solution is a reduced graphene oxide spinning solution, and the preparation method thereof comprises:
[0017] The graphite raw material is oxidized by a modified Hummers method to obtain graphene oxide;
[0018] The graphene oxide is chemically reduced and concentrated to obtain a reduced graphene oxide spinning solution.
[0019] Preferably, the method for preparing the shell spinning solution comprises:
[0020] The cellulose raw material is pretreated using a choline chloride / phthalic acid deep eutectic solvent system, and then sulfuric acid is added for hydrolysis to obtain a hydrolyzate;
[0021] Slowly add TEMPO and NaBr to the hydrolyzate and stir evenly; then dropwise add NaClO solution for surface modification, centrifuge and concentrate to obtain the nanocellulose spinning solution;
[0022] Wherein, the molar ratio of choline chloride to phthalic acid is 1:0.2-0.6.
[0023] Preferably, the coaxial wet spinning process is:
[0024] The mass ratio of the two-dimensional layered material in the core layer spinning solution to the nanocellulose in the shell layer spinning solution is (5-6):3;
[0025] The propulsion speed of the core layer spinning solution is 0.5-0.6 mL / min;
[0026] The propulsion speed of the shell spinning solution is 0.7-0.8 mL / min.
[0027] Preferably, the coagulation bath is a mixed liquid of acetic acid and N,N-dimethylformamide in a volume ratio of 1:1, and the temperature of the coagulation bath is -25 to -5°C;
[0028] The temperature of the low-temperature drying is -40 to -20°C, and the drying time is 30 to 40 hours.
[0029] Preferably, the core layer spinning solution is Ti3C2T x When MXene is used as spinning solution, its concentration is 12.5-15.5 mg / mL;
[0030] When the core layer spinning solution is a reduced graphene oxide spinning solution, its concentration is 18.5 to 21.2 mg / mL;
[0031] The concentration of the shell spinning solution is 23.5-29.7 mg / mL.
[0032] The third aspect of the present application provides the use of the above-mentioned fiber material for shielding terahertz waves or the fiber material for shielding terahertz waves prepared by the above-mentioned preparation method in smart wearable devices.
[0033] Compared with the prior art, the beneficial effects of this application are:
[0034] The fiber material for shielding terahertz waves of the present application uses a two-dimensional layered material as a core layer and wraps a nanocellulose shell layer skeleton to form a two-dimensional layered material@nanocellulose coaxial fiber, and the core layer Ti3C2T x The conductive layered structure of MXene and reduced graphene oxide remains intact. It not only has excellent electromagnetic shielding performance, with an effective shielding bandwidth covering the 0.1-1.5THz band, and an average shielding effectiveness of 47.61dB in this band; it also has excellent mechanical properties, with a tensile strength of 161.6MPa and an elongation at break of 5%.
[0035] This application uses a mixed coagulation bath of acetic acid and N,N-dimethylformamide and a specific spinning process to perform coaxial wet spinning, which not only has a significant optimization effect on the cross-linking and curing of the two-dimensional layered material @ nanocellulose coaxial fiber, which is beneficial to the construction of coaxial fibers, but also further improves its mechanical properties. In addition, by adjusting the concentration of the core layer spinning solution and the shell layer spinning solution, the terahertz wave shielding performance of the fiber material can be regulated to meet different electromagnetic interference shielding performance requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0037] Figure 1 Ti3C2T for this application x Physical pictures of MXene@nanocellulose coaxial fibers and reduced graphene oxide@nanocellulose coaxial fibers;
[0038] Figure 2 Ti3C2T for this application x Cross-sectional scanning electron microscopy images of MXene@nanocellulose coaxial fibers and reduced graphene oxide@nanocellulose coaxial fibers;
[0039] Figure 3 Ti3C2T for this application x MXene@nanocellulose coaxial fibers, reduced graphene oxide@nanocellulose coaxial fibers, Ti3C2T x Tensile stress-strain test curves of MXene fiber and reduced graphene oxide fiber;
[0040] Figure 4 Ti3C2T for this application x MXene@ nanocellulose coaxial fibers, Ti3C2Tx XRD comparison and Raman comparison of MXene fiber and reduced graphene oxide fiber;
[0041] Figure 5 Ti3C2T for this application x The electromagnetic shielding performance test diagram of MXene@nanocellulose coaxial fiber in the terahertz band (0.1~1.5THz);
[0042] Figure 6 XRD comparison chart and Raman comparison chart of reduced graphene oxide@nanocellulose coaxial fiber, reduced graphene oxide fiber and nanocellulose fiber;
[0043] Figure 7 This is a test diagram of the electromagnetic shielding performance of the reduced graphene oxide@nanocellulose coaxial fiber of the present application in the terahertz band (0.1-1.5 THz). DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0045] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.
[0046] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0047] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0048] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0049] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0050] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.
[0051] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0052] In a first aspect, the present application provides a fiber material for shielding terahertz waves, wherein the fiber material for shielding terahertz waves is a coaxial core-shell structure; the core layer is a two-dimensional layered material, and the shell layer is nanocellulose;
[0053] Wherein, the two-dimensional layered material includes Ti3C2T x MXene or reduced graphene oxide. In the present application, the radius of the core layer is 60-65 μm, the radius of the shell layer is 65-70 μm, and the core layer and the shell layer are tightly connected.
[0054] The fiber material for shielding terahertz waves of the present application uses a two-dimensional layered material as a core layer, and wraps a nanocellulose shell skeleton to form a two-dimensional layered material @ nanocellulose coaxial fiber. Among them, two-dimensional layered materials, such as MXene and reduced graphene oxide, have excellent electromagnetic interference shielding performance due to their excellent conductivity and two-dimensional layered structure, but due to high porosity, low orientation and weak interlayer van der Waals force, their mechanical properties are low. The present application forms a strong support by coating the nanocellulose shell layer on the surface of the two-dimensional layered material as a skeleton, so that the two-dimensional layered material is closely combined with the nanocellulose, which not only has good electromagnetic interference shielding performance, but also gives it excellent mechanical properties, and also has good processability, and can be used in flexible intelligent wearable shielding devices, which can maximize the comfort of wearing of intelligent wearable devices, functional integration and environmental adaptability.
[0055] In a second aspect, the present application provides a method for preparing the above-mentioned fiber material for shielding terahertz waves, comprising:
[0056] Step 1: prepare a core layer spinning solution using a two-dimensional layered material, and prepare a shell layer spinning solution using nanocellulose. In the present application, a core layer spinning solution is prepared using a two-dimensional layered material, specifically by Ti3C2T x MAX preparation of Ti3C2T x MXene spinning solution, or reduced graphene oxide spinning solution prepared by graphite raw material.
[0057] By Ti3C2T x MAX preparation of Ti3C2T x MXene spinning solution, and the method comprising:
[0058] S1, Ti3C2T x MAX is chemically etched by an etchant, and the etchant is removed by centrifugation and water washing; anhydrous ethanol is then added for intercalation treatment, and the precipitate is collected by centrifugation to obtain a multilayer Ti3C2T x MXene;
[0059] The etchant is HF, or a mixture of fluoride and acid such as a mixture of LiF and HCl. In the embodiment of the present application, the etchant is preferably a mixture of LiF and HCl. x MAX etching for 30 to 36 hours, centrifuge the etched liquid at 3500 rpm for 5 to 10 minutes, wash with deionized water to remove the etchant, and centrifuge several times until the pH of the supernatant is about 7. Add anhydrous ethanol to the solid phase, ultrasonically treat for 1 to 2 hours, and then centrifuge at 10000 rpm for 5 to 10 minutes to collect the lower precipitate to obtain a multilayer Ti3C2T x MXene.
[0060] S2, to multilayer Ti3C2T x Deionized water was added to MXene, and the black upper liquid was collected after multiple centrifugation to obtain Ti3C2T x MXene spinning solution.
[0061] Specifically, the multilayer Ti3C2T x Deionized water was added to MXene, and the mixture was mechanically shaken and ultrasonically treated for 20 to 30 minutes, and then centrifuged at 3500 rpm for 5 to 10 minutes to collect the upper black liquid; deionized water was added to the precipitate, and the mixture was mechanically shaken and ultrasonically treated for 20 to 30 minutes, and then centrifuged at 3500 rpm for 5 to 10 minutes to collect the upper black liquid. Repeat the above steps and collect the upper black liquid to obtain Ti3C2T x The MXene spinning solution preferably has a concentration of 12.5 to 15.5 mg / mL.
[0062] The reduced graphene oxide spinning solution is prepared by using graphite raw material, and the preparation method thereof comprises:
[0063] S1, oxidizing the graphite raw material by an improved Hummers method to obtain graphene oxide;
[0064] The graphite raw material, NaNO3 and concentrated H2SO4 are stirred in an ice water bath for pre-oxidation treatment, and then KMnO4 is added in batches, and then further reacted at 60°C, water is added, and stirred evenly; then H2O2 is added, and stirred evenly to obtain a graphene oxide solution;
[0065] The graphite raw material can be any one of flake graphite, natural graphite or expanded graphite, or a mixture of two or more thereof.
[0066] S2, graphene oxide is chemically reduced and concentrated to obtain reduced graphene oxide spinning solution.
[0067] Repeat centrifugation with deionized water for 4 to 5 times to purify the graphene oxide solution; add ascorbic acid to the graphene oxide solution for reduction to obtain a reduced graphene oxide spinning solution with a concentration of 18.5 to 21.2 mg / mL.
[0068] Wherein, the volume ratio of graphene oxide solution to ascorbic acid (99.7%) is 1:15.
[0069] In the present application, nanocellulose is used to prepare a shell spinning solution, and the preparation method thereof includes:
[0070] S1, using choline chloride / phthalic acid deep eutectic solvent system to pretreat the cellulose raw material at 140-160°C, and then adding sulfuric acid to hydrolyze at 45-55°C to obtain a hydrolyzate; wherein the cellulose raw material can be selected from cotton, hemp, bamboo, wood and other materials, and in the embodiment of the present application, elm wood powder is preferred, and the particle size thereof is 40-60 mesh.
[0071] Add the cellulose raw material to a deep eutectic solvent system with a molar ratio of choline chloride and phthalic acid of 1:0.2-0.6, and stir at 140-160°C for 2-4 hours. After pretreatment, hemicellulose and lignin are dissolved from the cellulose raw material, anhydrous ethanol is added and stirred continuously, and then washed and filtered with an ethanol / water solution until neutral. Add sulfuric acid at 45-55°C to hydrolyze the hemicellulose and lignin to obtain a hydrolyzate;
[0072] S2, slowly adding TEMPO and NaBr to the hydrolyzate, stirring evenly to obtain a suspension; then dropping NaClO solution into the suspension for surface modification, and obtaining nanocellulose slurry after centrifugation and concentration, i.e., shell spinning solution;
[0073] The corresponding relationship between the amount of TEMPO, NaBr and wood powder is: 0.25 mmol of TEMPO per gram of wood powder, and 0.8 mmol of NaBr per gram of wood powder.
[0074] The pH of the suspension is adjusted to 9, and NaClO solution is added to the suspension at room temperature every 5 minutes for surface modification until the concentration of NaClO in the suspension is 8-10 mmol / g. The suspension is then rapidly centrifuged at a speed of 5000 rpm, and repeated 4 times to obtain nanocellulose slurry, i.e., shell spinning solution, preferably with a concentration of 23.5-29.7 mg / mL.
[0075] Step 2, preparing raw fibers by coaxial wet spinning of the core layer spinning solution and the shell layer spinning solution, and solidifying the raw fibers in a coagulation bath and drying at low temperature to obtain fiber materials.
[0076] In the present application, the coagulation bath is a mixed liquid of acetic acid and N,N-dimethylformamide in a volume ratio of 1:1, and the temperature of the coagulation bath is -25 to -5°C; the temperature of the low-temperature drying is -40 to -20°C, and the drying time is 30 to 40 hours.
[0077] In the present application, the mass ratio of the two-dimensional layered material in the core layer spinning solution to the nanocellulose in the shell layer spinning solution is preferably (5-6): 3. In the coaxial wet spinning, the propulsion speed of the core layer spinning solution is 0.5-0.6 mL / min; the propulsion speed of the shell layer spinning solution is 0.7-0.8 mL / min.
[0078] Under the process conditions of this application, long-sized two-dimensional layered materials @ nanocellulose coaxial fibers can be stably and continuously spun, and the "core-shell" structure is tightly connected without destroying the core layer Ti3C2T x Conductive layered structures of MXene and reduced graphene oxide.
[0079] This application uses a mixed coagulation bath of acetic acid and N,N-dimethylformamide and a specific spinning process to perform coaxial wet spinning, which not only has a significant optimization effect on the cross-linking and curing of the two-dimensional layered material @ nanocellulose coaxial fiber, which is beneficial to the construction of coaxial fibers, but also further improves its mechanical properties. In addition, by adjusting the concentration of the core layer spinning solution and the shell layer spinning solution, the terahertz wave shielding performance of the fiber material can be regulated to meet different electromagnetic interference shielding performance requirements.
[0080] The fiber material for shielding terahertz waves of the present application has an excellent average shielding effectiveness of 47.61dB in the 0.1-1.5THz band, and has high flexibility, a tensile strength of 161.6MPa, and an elongation at break of 5%. It has good processing performance and can be used to make smart wearable devices for electromagnetic interference shielding.
[0081] The present application is further described below by way of examples.
[0082] Example 1
[0083] This embodiment provides a fiber material for shielding terahertz waves, wherein the core layer is Ti3C2T x MXene, the shell layer is nanocellulose, and the preparation method thereof includes:
[0084] Preparation of Ti3C2T x MXene core layer spinning solution:
[0085] 1.5 g LiF was dissolved in 9 ml deionized water, and added to 27 ml HCl to prepare an etching solution. 1.5 g Ti3AlC2 was added to the etching solution, and magnetic stirring was performed at 35°C and 500 n / min for 36 hours to obtain a dispersion.
[0086] The dispersion was evenly divided into 6 50 ml centrifuge tubes, centrifuged at 3500 rpm for 5 min, the supernatant was removed, 40 ml of deionized water was added and centrifuged repeatedly until the pH of the supernatant was 7; 40 ml of anhydrous ethanol was added to each of the 6 centrifuge tubes, ultrasonicated for 1 h, centrifuged at 10000 rpm for 5 min, and the centrifugal precipitate was collected to obtain Ti3C2T x MXene;
[0087] Add 20 ml of deionized water to the centrifuged precipitate, shake it mechanically, and then ultrasonicate it for 20 minutes. Centrifuge it at 3500 rpm for 5 minutes, and collect the black upper liquid. Repeat adding deionized water to the precipitate until half of the centrifuge tube is filled and centrifuge it repeatedly to obtain Ti3C2T x MXene slurry, namely Ti3C2T x MXene core layer spinning solution, the concentration of which is 12.5 mg / mL.
[0088] Preparation of shell spinning solution:
[0089] 65 g of elm wood powder with a particle size of 40-60 mesh was added to a deep eutectic solvent system with a molar ratio of choline chloride to phthalic acid of 1:0.2 of 3.5 mol, and stirred at 150°C at a speed of 300 rpm for 3 hours for pretreatment; 30 mL of anhydrous ethanol was added to the pretreated solution, heated and stirred for 10 minutes, and then washed and filtered with 120 ml of ethanol / water solution until neutral; hydrolyzed with 98% sulfuric acid at 50°C for 1 hour, and mechanically stirred for 30 minutes to obtain a hydrolyzate;
[0090] Slowly add 20mmol of TEMPO and 64mmol of NaBr to the hydrolyzate, stir at a speed of 1000n / min to obtain a suspension; adjust the pH of the suspension to 9, and add NaClO solution to the suspension every 5min at room temperature until the concentration of NaClO in the suspension is 10mmol / g. Then, the suspension is rapidly centrifuged at a speed of 5000rpm, and repeated 4 times to obtain a nanocellulose slurry, i.e., a nanocellulose spinning solution, with a concentration of 23.5mg / mL.
[0091] Coaxial wet spinning:
[0092] Ti3C2T x MXene slurry was used as the core spinning solution, nanocellulose slurry was used as the shell spinning solution, and appropriate amounts of Ti3C2T x MXene slurry and nanocellulose slurry were connected to a coaxial spinning needle (20G+18G, 0.98mm+1.22mm), and the extrusion of the core layer and shell layer spinning solutions in the coaxial spinning needle was controlled at propulsion speeds of 0.5mL / min and 0.7mL / min, respectively. The slurry was solidified in a mixed coagulation bath (volume ratio of 1:1) of acetic acid (concentration of 99.7%) / N,N-dimethylformamide (concentration of 99.5%) at -20°C, and dried at -35°C for 35h to obtain Ti3C2T x MXene@nanocellulose coaxial fiber, that is, the fiber material used for shielding terahertz waves in the present application.
[0093] Example 2
[0094] The difference between Example 2 and Example 1 is that in the preparation of Ti3C2T x In the MXene core layer spinning solution step, the amount of Ti3AlC2 was changed to 1.8 g, and the rest was the same as in Example 1. x MXene slurry with a concentration of 13.2 mg / mL.
[0095] Example 3
[0096] The difference between Example 3 and Example 1 is that in the preparation of Ti3C2T x In the MXene core layer spinning solution step, the amount of Ti3AlC2 was changed to 1.9 g, and the rest was the same as in Example 1. x MXene slurry with a concentration of 13.8 mg / mL.
[0097] Example 4
[0098] The difference between Example 4 and Example 1 is that in the preparation of Ti3C2T x In the MXene core layer spinning solution step, the amount of Ti3AlC2 was changed to 2 g, the amount of LiF was changed to 2 g, and the amount of HCl was changed to 30 mL, and the rest was the same as in Example 1. x MXene slurry with a concentration of 14.4 mg / mL.
[0099] Example 5
[0100] The difference between Example 5 and Example 1 is that in the preparation of Ti3C2T x In the MXene core layer spinning solution step, the amount of Ti3AlC2 was changed to 2.4 g, the amount of LiF was changed to 2.2 g, and the amount of HCl was changed to 33 mL. The rest was the same as in Example 1. x MXene slurry with a concentration of 15.5 mg / mL.
[0101] Example 6
[0102] The difference between Example 6 and Example 1 is that in the step of preparing the shell spinning solution, the molar ratio of choline chloride to phthalic acid is changed to 1:0.3, the concentration of NaClO in the suspension is changed to 8 mmol / g, and the rest is the same as Example 1. The concentration of the shell spinning solution prepared in Example 6 is 24.2 mg / mL.
[0103] Example 7
[0104] The difference between Example 7 and Example 1 is that in the step of preparing the shell spinning solution, the molar ratio of choline chloride to phthalic acid is changed to 1:0.4, the concentration of NaClO in the suspension is changed to 8 mmol / g, and the rest is the same as Example 1. The shell spinning solution prepared in Example 7 has a concentration of 24.9 mg / mL.
[0105] Example 8
[0106] The difference between Example 8 and Example 1 is that in the step of preparing the shell spinning solution, the molar ratio of choline chloride to phthalic acid is changed to 1:0.5, the concentration of NaClO in the suspension is changed to 8 mmol / g, and the rest is the same as Example 1. The shell spinning solution prepared in Example 8 has a concentration of 25.3 mg / mL.
[0107] Example 9
[0108] The difference between Example 9 and Example 1 is that in the step of preparing the shell spinning solution, the molar ratio of choline chloride to phthalic acid is changed to 1:0.6, and the rest is the same as Example 1. The shell spinning solution prepared in Example 9 has a concentration of 26.1 mg / mL.
[0109] Example 10
[0110] This embodiment provides a fiber material for shielding terahertz waves, wherein the core layer is reduced graphene oxide and the shell layer is nanocellulose. The preparation method thereof includes:
[0111] Preparation of reduced graphene oxide core layer spinning solution:
[0112] 8g of natural flake graphite and 4.5g of NaNO3 were dispersed in 145mL of concentrated H2SO4, and mechanically stirred in an ice-water bath for 10h for pre-oxidation treatment; after pre-oxidation treatment, 24g of KMnO4 was added in batches within 30min, and stirred continuously for 60min, and further reacted in an oven at 60℃ for 5h. Then deionized water was added to the reaction solution and stirred evenly; then 30mL of H2O2 was added to the reaction solution at a temperature of 45℃ to obtain a graphene oxide solution;
[0113] The graphene oxide solution was purified by repeated centrifugation with deionized water for 5 times, and ascorbic acid was added for reduction in a ratio of 1:15 between the graphene oxide solution and ascorbic acid (99.7%) to obtain a core layer spinning solution reduced graphene oxide slurry with a concentration of about 18.5 mg / mL.
[0114] Preparation of shell spinning solution:
[0115] 80 g of elm wood powder with a particle size of 40-60 mesh was added to a deep eutectic solvent system with a molar ratio of choline chloride to phthalic acid of 3.5 mol and stirred at 150°C and 500 rpm for 1 hour for pretreatment; 20 mL of anhydrous ethanol was added to the pretreated solution, heated and stirred for 30 minutes, and then washed and filtered with 150 ml of ethanol / water solution until neutral; hydrolyzed with 98% sulfuric acid at 80°C for 1 hour, and mechanically stirred for 30 minutes to obtain a hydrolyzate;
[0116] Slowly add (0.3 mmol / g) of TEMPO and (0.9 mmol / g) of NaBr to the hydrolyzate, stir at a speed of 1000 n / min to obtain a suspension; adjust the pH of the suspension to 9, and add NaClO solution dropwise to the suspension every 5 min at room temperature until the concentration of NaClO in the suspension is 10 mmol / g.
[0117] The suspension was then rapidly centrifuged at a rotation speed of 5000 rpm, and the process was repeated 4 times to obtain a nanocellulose slurry, namely a nanocellulose spinning solution, with a concentration of 23.5 mg / mL.
[0118] Coaxial wet spinning:
[0119] Reduced graphene oxide slurry is used as the core layer spinning liquid, and nanocellulose slurry is used as the shell layer spinning liquid. Appropriate amounts of reduced graphene oxide slurry and nanocellulose slurry are taken with syringes respectively, and a coaxial spinning needle (20G+18G, 0.98mm+1.22mm) is connected. The extrusion of the core layer and shell layer spinning liquids in the coaxial spinning needle is controlled at propulsion speeds of 0.6mL / min and 0.8mL / min respectively, and the fibers are cured in a mixed coagulation bath (volume ratio of 1:1) of acetic acid (concentration of 99.7%) / N,N-dimethylformamide (concentration of 99.5%) at -20°C, and dried at -35°C for 35h to obtain reduced graphene oxide@nanocellulose coaxial fibers, i.e., the fiber material for shielding terahertz waves of the present application.
[0120] Embodiment 11
[0121] The difference between Example 11 and Example 10 is that in the step of preparing the reduced graphene oxide core layer spinning solution, the amount of natural flake graphite is changed to 10g, the amount of NaNO3 is changed to 5.6g, the amount of concentrated H2SO4 is changed to 180mL, and the amount of KMnO4 is changed to 30g, and the rest is the same as Example 10.
[0122] The reduced graphene oxide core layer spinning solution of Example 11 has a concentration of 19.2 mg / mL.
[0123] Example 12
[0124] The difference between Example 12 and Example 10 is that in the step of preparing the reduced graphene oxide core layer spinning solution, the amount of natural flake graphite is changed to 15g, the amount of NaNO3 is changed to 8.4g, the amount of concentrated H2SO4 is changed to 270mL, and the amount of KMnO4 is changed to 45g, and the rest is the same as Example 10.
[0125] The reduced graphene oxide core layer spinning solution of Example 12 has a concentration of 19.7 mg / mL.
[0126] Example 13
[0127] The difference between Example 13 and Example 10 is that in the step of preparing the reduced graphene oxide core layer spinning solution, the amount of natural flake graphite is changed to 20g, the amount of NaNO3 is changed to 11.2g, the amount of concentrated H2SO4 is changed to 360mL, and the amount of KMnO4 is changed to 60g, and the rest is the same as Example 10.
[0128] The reduced graphene oxide core layer spinning solution of Example 13 has a concentration of 20.5 mg / mL.
[0129] Embodiment 14
[0130] The difference between Example 14 and Example 10 is that in the step of preparing the reduced graphene oxide core layer spinning solution, the amount of natural flake graphite is changed to 25g, the amount of NaNO3 is changed to 14g, the amount of concentrated H2SO4 is changed to 450mL, and the amount of KMnO4 is changed to 75g, and the rest is the same as Example 10.
[0131] The reduced graphene oxide core layer spinning solution of Example 14 has a concentration of 21.2 mg / mL.
[0132] Embodiment 15
[0133] The difference between Example 15 and Example 10 is that in the step of preparing the shell spinning solution, the molar ratio of choline chloride to phthalic acid is changed to 1:0.3, and the rest is the same as Example 10. The concentration of the shell spinning solution in Example 15 is 27.2 mg / mL.
[0134] Example 16
[0135] The difference between Example 16 and Example 10 is that in the step of preparing the shell spinning solution, the molar ratio of choline chloride to phthalic acid is changed to 1:0.4, and the rest is the same as Example 10. The concentration of the shell spinning solution in Example 16 is 28.1 mg / mL.
[0136] Embodiment 17
[0137] The difference between Example 17 and Example 10 is that in the step of preparing the shell spinning solution, the molar ratio of choline chloride to phthalic acid is changed to 1:0.5, and the rest is the same as Example 10. The concentration of the shell spinning solution in Example 17 is 28.9 mg / mL.
[0138] Embodiment 18
[0139] The difference between Example 18 and Example 10 is that in the step of preparing the shell spinning solution, the molar ratio of choline chloride to phthalic acid is changed to 1:0.6, and the rest is the same as Example 10. The concentration of the shell spinning solution in Example 18 is 29.7 mg / mL.
[0140] Comparative Example 1
[0141] Use a syringe to take an appropriate amount of Ti3C2T prepared in Example 1 x The MXene core layer spinning solution was connected to a wet spinning needle (18G, 1.22 mm), and the spinning solution in the wet spinning needle was extruded at a propulsion speed of 0.6 mL / min. The solution was solidified in a mixed coagulation bath (volume ratio 1:0.5) of acetic acid (concentration 99.7%) / N,N-dimethylformamide (concentration 99.5%) at -15 °C, and dried at -35 °C for 35 h to obtain Ti3C2T x MXene nanofibers.
[0142] Comparative Example 2
[0143] Use a syringe to take an appropriate amount of the reduced graphene oxide core layer spinning solution prepared in Example 10, use a syringe to take an appropriate amount of reduced graphene oxide slurry, connect a wet spinning needle (18G, 1.22mm), control the extrusion of the spinning solution in the wet spinning needle at a propulsion speed of 0.7mL / min, and solidify it in a mixed coagulation bath (volume ratio of 1:0.8) of acetic acid (concentration of 99.7%) / N,N-dimethylformamide (concentration of 99.5%) at -15°C, and dry it at -35°C for 35h to obtain reduced graphene oxide nanofibers.
[0144] In the present application, the fiber material for shielding terahertz waves prepared in Examples 1-9 is Ti3C2T x MXene@nanocellulose coaxial fiber; The fiber material for shielding terahertz waves prepared in Examples 10-18 is reduced graphene oxide@nanocellulose coaxial fiber.
[0145] Ti3C2T prepared in Example 1 x MXene@nanocellulose coaxial fibers and the actual images of reduced graphene oxide@nanocellulose coaxial fibers prepared in Example 10 are shown in FIG. Figure 1 As shown. Among them, Figure 1Ti3C2T on the left x MXene@nanocellulose coaxial fiber, on the right is reduced graphene oxide@nanocellulose coaxial fiber.
[0146] from Figure 1 It can be seen that the prepared single long Ti3C2T x The macroscopic morphology of MXene@nanocellulose and reduced graphene oxide@nanocellulose coaxial fibers is relatively good.
[0147] Ti3C2T prepared in Example 1 x The cross-sectional scanning electron microscopy images of MXene@nanocellulose coaxial fibers and reduced graphene oxide@nanocellulose coaxial fibers prepared in Example 10 are shown in FIG. Figure 2 As shown, Figure 2 The middle (a) figure is Ti3C2T x (a) Scanning electron micrograph of the cross section of MXene@nanocellulose coaxial fibers, (b) Scanning electron micrograph of the cross section of reduced graphene oxide@nanocellulose coaxial fibers.
[0148] from Figure 2 It can be seen that the prepared single Ti3C2T x The core-shell structure of MXene@nanocellulose and reduced graphene oxide@nanocellulose coaxial fibers is intact, the core layer and the shell layer are tightly connected, and the Ti3C2T x The conductive layered structures of MXene and reduced graphene oxide are intact.
[0149] The Ti3C2T prepared in Example 1 x MXene@nanocellulose coaxial fibers, reduced graphene oxide@nanocellulose coaxial fibers prepared in Example 10, Ti3C2T x The mechanical properties of the MXene fiber and the reduced graphene oxide fiber of comparative example 2 were tested, and their tensile stress-strain test curves were as follows: Figure 3 shown.
[0150] from Figure 3 It can be seen that Ti3C2T x The toughness of MXene fibers and reduced graphene oxide nanofibers is low, with tensile strengths of 63.6 MPa and 77.2 MPa, and elongations at break of approximately 1.97% and 2.42%, respectively. x MXene@nanocellulose coaxial fibers and reduced graphene oxide@nanocellulose coaxial fibers showed significantly improved flexibility, with tensile strengths of 130.5 MPa and 161.6 MPa, respectively, and elongations at break increased to 5% and 4.7%, respectively.
[0151] Ti3C2T prepared in Example 1 x MXene@nanocellulose coaxial fibers and Ti3C2T x The XRD comparison and Raman comparison of MXene nanofibers and nanocellulose are shown in the figure. Figure 4 As shown, Figure 4 (a) is the XRD comparison chart, and (b) is the Raman comparison chart.
[0152] from Figure 4 It can be seen that Ti3C2T x Ti3C2T in MXene@nanocellulose coaxial fibers x The cross-linking between the MXene core layer and the nanocellulose shell layer causes the shell to shift, thereby reducing the distance between the layers and increasing the density. x MXene@nanocellulose coaxial fibers exhibited better mechanical properties.
[0153] Ti3C2T prepared in test examples 1-9 x The electromagnetic shielding performance of MXene@ nanocellulose coaxial fiber in the terahertz band (0.1-1.5THz) is shown in the test figure. Figure 5 The average electromagnetic shielding effectiveness data are shown in Table 1 and Table 2. Among them, Examples 1-5 are different Ti3C2T x The average electromagnetic shielding effectiveness data of fiber materials with MXene concentration (12.5-15.5 mg / mL) are shown in Table 1.
[0154] Table 1 Different Ti3C2T x Average electromagnetic shielding effectiveness data of fiber materials with different MXene concentrations
[0155]
[0156] From Table 1, we can see that Ti3C2T x MXene@nanocellulose coaxial fibers with Ti3C2T x The increase in MXene concentration significantly increases its average electromagnetic shielding effectiveness against terahertz waves. However, when the MXene concentration is too high, it is easier to form agglomerations due to its high aspect ratio and high specific surface area, which leads to a decrease in electromagnetic shielding performance and mechanical properties.
[0157] Example 1 and Examples 6-9 are fiber materials with different nanocellulose concentrations (23.5-26.1 mg / mL), and their average electromagnetic shielding effectiveness data are shown in Table 2.
[0158] Table 2 Ti3C2T with different nanocellulose concentrations xAverage electromagnetic shielding effectiveness data of MXene@nanocellulose coaxial fibers
[0159]
[0160] From Table 2, we can see that Ti3C2T x MXene@nanocellulose coaxial fibers have little effect on the average electromagnetic shielding effectiveness of terahertz waves as the concentration of nanocellulose increases. It mainly plays the role of organic skeleton support and improves the Ti3C2T x Mechanical properties of MXene@nanocellulose coaxial fibers.
[0161] In the present application, the XRD comparison chart and Raman comparison chart of the reduced graphene oxide@nanocellulose coaxial fiber prepared in Example 10, the reduced graphene oxide fiber and the nanocellulose fiber are as follows: Figure 6 As shown, Figure 6 (a) is the XRD comparison chart, and (b) is the Raman comparison chart.
[0162] from Figure 6 It can be seen that the cross-linking effect between the reduced graphene oxide core layer and the nanocellulose shell layer in the reduced graphene oxide @ nanocellulose coaxial fibers also causes them to shift, thereby reducing the interlayer distance and improving the density. The reduced graphene oxide @ nanocellulose coaxial fibers exhibit better mechanical properties.
[0163] The electromagnetic shielding performance of the reduced graphene oxide@nanocellulose coaxial fibers prepared in Examples 10-18 in the terahertz band (0.1-1.5 THz) is tested. Figure 7 The average electromagnetic shielding effectiveness data are shown in Table 3 and Table 4. Among them, Examples 10-14 are fiber materials with different reduced graphene oxide concentrations (18.5-21.2 mg / mL), and the average electromagnetic shielding effectiveness data are shown in Table 3.
[0164] Table 3 Average electromagnetic shielding effectiveness data of fiber materials with different reduced graphene oxide concentrations
[0165]
[0166] It can be seen from Table 3 that the average electromagnetic shielding effectiveness of reduced graphene oxide@nanocellulose coaxial fibers against terahertz waves increases significantly with the increase of reduced graphene oxide concentration. However, when the reduced graphene oxide concentration is too high, it is easier to form agglomerations due to the high aspect ratio and high specific surface area, which leads to a decrease in electromagnetic shielding performance and mechanical properties.
[0167] Example 10 and Examples 15-18 are fiber materials with different nanocellulose concentrations (26.5-29.7 mg / mL), and their average electromagnetic shielding effectiveness data are shown in Table 4.
[0168] Table 4 Average electromagnetic shielding effectiveness data of reduced graphene oxide@nanocellulose coaxial fibers with different nanocellulose concentrations
[0169]
[0170] As can be seen from Table 4, as the concentration of nanocellulose increases, the average electromagnetic shielding effectiveness of the reduced graphene oxide @ nanocellulose coaxial fiber on the terahertz wave is not significantly affected. It mainly plays the role of organic skeleton support, which improves the mechanical properties of the reduced graphene oxide @ nanocellulose coaxial fiber.
[0171] The fiber material for shielding terahertz waves prepared in the present application not only has excellent electromagnetic shielding performance, with an effective shielding bandwidth covering the 0.1-1.5 THz band, within which the average shielding effectiveness can reach 47.61 dB, but also has excellent mechanical properties, with a tensile strength of up to 161.6 MPa and an elongation at break of up to 5%.
[0172] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.
Claims
1. A fiber material for shielding terahertz waves, characterized in that: It is a coaxial core-shell structure, the core layer is a two-dimensional layered material, and the shell layer is nanocellulose; The two-dimensional layered material includes Ti3C2T x MXene or reduced graphene oxide.
2. The fiber material for shielding terahertz waves according to claim 1, characterized in that: The radius of the core layer is 60-65 μm, and the radius of the shell layer is 65-70 μm.
3. The method for preparing the fiber material for shielding terahertz waves according to claim 1, characterized in that: include: The core spinning solution is prepared by using two-dimensional layered materials, and the shell spinning solution is prepared by using nanocellulose; The core layer spinning solution and the shell layer spinning solution are coaxially wet-spinned to obtain raw fibers, which are solidified in a coagulation bath and dried at low temperature to obtain fiber materials.
4. The preparation method according to claim 3, characterized in that: The core layer spinning solution is Ti3C2T x MXene spinning solution, the preparation method thereof comprises: Ti3C2T x MAX is chemically etched by an etchant, and the etchant is removed by centrifugation and water washing; anhydrous ethanol is then added for intercalation treatment, and the precipitate is collected by centrifugation to obtain a multilayer Ti3C2T x MXene; Towards multilayer Ti3C2T x Deionized water was added to MXene, and the black upper liquid was collected after multiple centrifugation to obtain Ti3C2T x MXene spinning solution.
5. The preparation method according to claim 3, characterized in that: The core layer spinning solution is a reduced graphene oxide spinning solution, and the preparation method thereof comprises: The graphite raw material is oxidized by a modified Hummers method to obtain graphene oxide; The graphene oxide is chemically reduced and concentrated to obtain a reduced graphene oxide spinning solution.
6. The preparation method according to claim 3, characterized in that: The method for preparing the shell spinning solution comprises: The cellulose raw material is pretreated using a choline chloride / phthalic acid deep eutectic solvent system, and then sulfuric acid is added for hydrolysis to obtain a hydrolyzate; Slowly add TEMPO and NaBr to the hydrolyzate and stir evenly; then dropwise add NaClO solution for surface modification, centrifuge and concentrate to obtain the nanocellulose spinning solution; Wherein, the molar ratio of choline chloride to phthalic acid is 1:0.2-0.
6.
7. The preparation method according to claim 3, characterized in that: The coaxial wet spinning process is: The mass ratio of the two-dimensional layered material in the core layer spinning solution to the nanocellulose in the shell layer spinning solution is (5-6):3; The propulsion speed of the core layer spinning solution is 0.5-0.6 mL / min; The propulsion speed of the shell spinning solution is 0.7-0.8 mL / min.
8. The preparation method according to claim 3, characterized in that: The coagulation bath is a mixed liquid of acetic acid and N,N-dimethylformamide in a volume ratio of 1:1, and the temperature of the coagulation bath is -25 to -5°C; The temperature of the low-temperature drying is -40 to -20°C, and the drying time is 30 to 40 hours.
9. The preparation method according to claim 3, characterized in that: The core layer spinning solution is Ti3C2T x When MXene is used as spinning solution, its concentration is 12.5-15.5 mg / mL; When the core layer spinning solution is a reduced graphene oxide spinning solution, its concentration is 18.5 to 21.2 mg / mL; The concentration of the shell spinning solution is 23.5-29.7 mg / mL.
10. Use of the fiber material for shielding terahertz waves according to claim 1 or 2 or the fiber material for shielding terahertz waves prepared by the preparation method according to claims 3 to 9 in smart wearable devices.